An evaluation of the benefits of high-quality cassava peel (HQCP) mash - International Livestock Research Institute (International Livestock Research Institute, 2022)
This video highlights the benefits of using high-quality cassava peel (HQCP) mash as animal feed shared by farmers and researchers in nigeria.